Adaptation of Some Clones of Sweet Potato (Ipomoea batatas L.) in the Lowlands and the Use of Manure - Mardhiah Hayati; . Sabarudin; . Efendi; Ashabu Anhar; Elly Kesumawati; Nur Kamalia (Syiah Kuala University, 2015)
This study aims to determine adaptation of some clones of sweet potato in the lowlands and the best manure application on the growth and yield of sweet potato as well as the interaction betweenthe two factors. Research conducted at the Experimental Field of the Faculty of Agriculture SyiahKuala University, Banda Aceh, with a height of 4 m above sea level, from March to September 2014. This study used a Randomized Complete Block Design in factorial arrangement (2x8), using a split plot design with three replications. The main plot is a manure treatment (control and manure 20 ton/ha), and the subplot is a treatment of types of sweet potato clones (CIP-LSQ, CIP-1945,CIP-MAN, CIP-153, CIP-CER, CIP-BDG), and local clones (beige and orange). The results showed that the best plant growth was found on CIP-153 clone, while the best crop production was CIP- LSQ clone. Growth and crop production was found best on control treatment. There are interactions between manure and clones on weight of the fresh shoot (ton/ha), fresh weight and dry bulb per plant (g), the weight of large tubers (ton/ha) and tubers yield (ton/ha). The best plant growth and production was found on a combination treatment of CIP-LSQ clones and control (without manure).